(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research depth and dimensions of the problem of environmental pollution resulting from the combustion of fuel used in electric power generators, especially in the summer and you are the national electric power supplied by almost non-existent state where this problem is a local phenomenon that has serious dimensions to human health, as well as the possibility of using a the tax system tools of b (environmental taxes) to reduce these pollutants, so the search is aimed at the types of gases emitted from burning fuel electric generators operating in the province of Baghdad and then measure the amount of environmental pollution as well as compared to the amount of some of these gases, which is more risk to humans with permitted by the World Health Organization and determine the recognizing environmental tax rate amounts and research reached a number of conclusions was the most important that the amount of gases that Atnjha combustion of the fuel used in diesel generators in the province of Baghdad exceed permitted by the World Health Organization quantities as well as there is a basic truth: is that environmental taxes will pay workers in this field on the reduction of greenhouse gas emissions resulting from fuel which is considered one of the main causes of environmental pollution combustion In light of these findings, we recommend a number of recommendations, the most important of the need to develop environmental legislation enacting deterrent laws to suit the current time and limit the behavior of abusers as well as the need for environmental tax applied next to a number of rules and regulatory standards, especially in some cases result in serious environmental damage, as in these cases, the prevention or urban provider to collect the tax.